Spectroscopic studies and molecular docking on the interaction of delphinidin‐3‐O‐galactoside with tyrosinase. (9th June 2021) - Chen, Rongda; Shi, Yurui; Liu, Guiming; Tao, Yanzhou; Fan, Yangyang; Wang, Xiaolin; Li, Li
Abstract: The inhibitory effects of delphinidin‐3‐O‐galactoside (DG) on the activities of tyrosinase (EC 1.14.18.1) (TY) from the edible Agaricus bisporus mushroom were investigated by enzyme kinetics, multispectroscopic methods, and molecular docking. As a result, DG showed strong inhibition on TY with the IC50 of 34.14 × 10 –6 mol L –1 . The inhibition mode of DG against TY was mixed type with α values of 5.09. The binding constant K a and related thermodynamic parameters at the three different temperatures showed that the fluorescence quenching of TY by DG was static quenching. Synchronous fluorescence, three‐dimensional fluorescence, ultraviolet–visible spectroscopy, and circular dichroism spectroscopies confirmed that the conformation or microenvironment of the TY protein were changed after binding with DG. Molecular docking revealed that DG had strong binding affinity to TY through hydrogen bonding and van der Waals force, and the results were consistent with the fluorescence data. Our findings suggested that DG may be potential TY inhibitor.